2017
DOI: 10.1209/0295-5075/119/53001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Rydberg hydrogen atom near a topologically insulating surface

Abstract: -Interactions of atoms and molecules with surfaces PACS 05.45.-a -Nonlinear dynamical systems and chaos PACS 11.15.Yc -Chern-Simons gauge theory Abstract -We investigate the classical dynamics of a Rydberg hydrogen atom near the surface of a planar topological insulator. The system is described by a Hamiltonian consisting of the freehydrogen part and the hydrogen-surface potential. The latter includes the interactions between the electron and both image electric charges and image magnetic monopoles. Owing to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…This is consistent with previous calculations which show that Casimir forces can be repulsive if they involve magnetic moments couplings [56,57]. In a similar fashion, it was recently shown that the dynamical properties of the atomic electron can be tuned with the TMEP θ [58]. For the TI TlBiSe 2 we obtain V CPmax = 4.2 Hz, which is 10 −2 smaller than the theoretical uncertainty in the splitting of the 2P 3/2 line.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous calculations which show that Casimir forces can be repulsive if they involve magnetic moments couplings [56,57]. In a similar fashion, it was recently shown that the dynamical properties of the atomic electron can be tuned with the TMEP θ [58]. For the TI TlBiSe 2 we obtain V CPmax = 4.2 Hz, which is 10 −2 smaller than the theoretical uncertainty in the splitting of the 2P 3/2 line.…”
Section: Discussionsupporting
confidence: 92%
“…The present work relies on the idea that atomic spectroscopy could play an important role in the study of the TME in axionic matter, as proposed in Refs. [34] and [35]. We consider it as providing an idealized setup where one can acquire a qualitative understanding of the orders of magnitude involved, together with a general idea of the major modifications to be expected in the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…However, when an atom is close to the interface between two θ-media, Maxwell's equations acquire additional magnetoelectric terms which yields to new interactions between the atomic electron and the interface, besides the usual nucleus-electron electromagnetic interaction. This problem has been tackled recently from both a classical [34] and a quantum perturbative [35] perspectives, but an analytic treatment of the quantum-mechanical problem is still absent. Our main aim here is to fill in this gap.…”
Section: The Quantum Mechanical Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…26. The classical dynamics of a Rydberg hydrogen atom near a planar TI has also been investigated 27 .…”
Section: Introductionmentioning
confidence: 99%